The Paper Implementation of the Competence Model of the Educational Standards in Geography (DGfG)–An Analysis of the Advancement of the Bavarian Grammar School Curriculum in Geography Towards the Competence-Oriented LehrplanPLUS - Schöps, Andreas (Journal of Geography Education, 2017)
When the Educational Standards in Geography for the Intermediate School Certificate were published for the first time in 2006, a successive implementation process was expected. One result sought was the integration of the Educational Standards in both school lessons as well as in formal contexts such as the curricula. However, as of today, there is a considerable lack in according research findings of such a paper implementation, and the question of the particular impact of the Educational Standards on the curricula of the different types of schools within Germany remains mostly unanswered. In the article presented here, the Bavarian grammar school (Gymnasium) curriculum Geography of 2004 (slightly alternated in 2009) is compared to the new curriculum LehrplanPLUS Geography, which is due to be implemented in 2017, with a particular focus on the formal implementation of the competence model of the Educational Standards. From an overall perspective, the study can be regarded as a contribution to an emerging school of didactic implementation research. A newly developed research tool set to analyze formal paper implementation results based on concepts of a qualitative content analysis. As the results presented reveal, the overall implementation and integration of the competence model of the Educational Standards into the new Bavarian Geography curriculum (Gymnasium) via paper implementation can be confirmed. Yet, a more detailed view shows that the level of re-installment varies, from high (areas of competence) to lower (particular standards), with significant differences concerning the particular single abilities.